The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-11051-0
|View full text |Cite
|
Sign up to set email alerts
|

Projection Stereolithographic Fabrication of BMP-2 Gene-activated Matrix for Bone Tissue Engineering

Abstract: Currently, sustained in vivo delivery of active bone morphogenetic protein-2 (BMP-2) protein to responsive target cells, such as bone marrow-derived mesenchymal stem cells (BMSCs), remains challenging. Ex vivo gene transfer method, while efficient, requires additional operation for cell culture and therefore, is not compatible with point-of-care treatment. In this study, two lentiviral gene constructs – (1) Lv-BMP/GFP, containing human BMP-2 and green fluorescent protein (GFP) gene (BMP group); or (2) Lv-GFP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…SLA is a great option for highly detailed scaffolds, requiring tight tolerances and smooth surfaces, such as molds, patterns, and functional parts, as it can achieve a spatial resolution of approximately 50 μm [ 25 ]. Various techniques that fall under SLA, include: two-photon polymerization (2PP) [ 25 ], holography [ 27 ], and visible light-based [ 28 ] techniques. The various SLA techniques offer different possibilities, such as improved resolutions of up to 200 nm with 2PP or the use of visible light to avoid the negative impact of UV light on cells.…”
Section: Stereolithographymentioning
confidence: 99%
“…SLA is a great option for highly detailed scaffolds, requiring tight tolerances and smooth surfaces, such as molds, patterns, and functional parts, as it can achieve a spatial resolution of approximately 50 μm [ 25 ]. Various techniques that fall under SLA, include: two-photon polymerization (2PP) [ 25 ], holography [ 27 ], and visible light-based [ 28 ] techniques. The various SLA techniques offer different possibilities, such as improved resolutions of up to 200 nm with 2PP or the use of visible light to avoid the negative impact of UV light on cells.…”
Section: Stereolithographymentioning
confidence: 99%
“…In recent years, the researches of stem cells have provided new ideas for bone tissue engineering ( 27 , 28 ). It has been confirmed that BMSCs has significant differentiation ability of osteoblasts in vitro in the treatment of specific chemical substances including β-phosphoglycerol, dexamethasone and vitamin C; cytokines and mechanical mechanics stimulation ( 28 , 29 ). Many factors including cytokines can induce BMSCs to differentiate into osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors including cytokines can induce BMSCs to differentiate into osteoblasts. The most important one of the cytokines are BMPs ( 28 , 30 ). BMP is a major regulatory factor for the differentiation of BMSCs into osteoblasts among a number of factors that activate or inhibit the osteoblastic signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the cationic nature of CS elicits an efficient complexation with DNA molecules making it an ideal candidate for gene delivery (Di Martino et al, 2005). Successful CS-pDNA complexation and sustained transfection of MSCs makes CS a promising vector also for gene activated matrices (GAMs), which are scaffolds engineered to provide a direct and sustained delivery of nucleic acids ensuring efficient and durable cell transfection in situ (Raisin et al, 2016;D'Mello et al, 2017;Lin et al, 2017). In particular, the encapsulation of plasmids into nano or micro-particulate CS-systems to be loaded within scaffolds could offer significant spatiotemporal control on the activity of the encoded biofactors (Peng et al, 2009).…”
Section: Matrices For Gene Deliverymentioning
confidence: 99%